Fact Sheet: First Arctic Science Ministerial (2016)
Science Ministers from 25 governments and the European Union gathered at the White House to discuss Arctic research priorities and sign a Joint Statement on increased international collaboration on Arctic science and inclusion of Indigenous peoples in understanding and responding to changes in the Arctic